2021
DOI: 10.1088/1742-6596/1967/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sequential and circular scanning thermal fields and their influence on microstructure of Alnico alloy produced by laser powder bed fusion

Abstract: Residual stress create deformations and stress in additive structures that lead to geometry deviations of created elements of 3D models and defects as pores and cracks that occur in construction process. Our work rests upon theoretical and experimental approach to the study. The main objective is to compare thermal fields with the microstructure of samples and to establish relationship between laser powder bed fusion (LPBF) modes and the structure of the samples to be created. 3D finite element method (FEM) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, despite these noteworthy density enhancements, the samples displayed surface defects, notably porosity and cracks in LPBF-processed Alnico-5 [56,57]. A similar scenario was observed when Alnico-8 was processed via LPBF with a heated stage at 800 °C, with evident porosity [34,59]. In contrast, Shakirov et al demonstrated that meticulous optimization of process parameters, specifically employing settings at 190 W and 700 mm/s, resulted in Alnico-5 samples with reduced porosity and cracks [57].…”
Section: Additive Manufacturing Of Alnicomentioning
confidence: 62%
See 2 more Smart Citations
“…However, despite these noteworthy density enhancements, the samples displayed surface defects, notably porosity and cracks in LPBF-processed Alnico-5 [56,57]. A similar scenario was observed when Alnico-8 was processed via LPBF with a heated stage at 800 °C, with evident porosity [34,59]. In contrast, Shakirov et al demonstrated that meticulous optimization of process parameters, specifically employing settings at 190 W and 700 mm/s, resulted in Alnico-5 samples with reduced porosity and cracks [57].…”
Section: Additive Manufacturing Of Alnicomentioning
confidence: 62%
“…Figure 15. Schematic of quasi-binary phase diagram of Alnico-8 with (α 1 ) and (α 2 ) [5].Table 6.The phases observed in Alnico samples fabricated through various processes for both the as-processed and post-heat treatment conditions[1,4,34,[54][55][56][57][58][59]91].ProcessingAs Processed (Microstructure)…”
mentioning
confidence: 99%
See 1 more Smart Citation